Transferencias condicionadas de dinero en Colombia: entre la política social y las lógicas de servidumbre - Leidy Yolanda González García (Revue de la Régulation)
This article aims to interrogate the multiple and complex social orders that social policy establishes and reproduces in Colombia through the conditional cash transfer program «Más familias en acción». For this, money from this program is chosen as an explanatory matrix that allows us to examine three analytical lines that are produced in the population receiving this type of monetary transfers, namely: social logic, moral positions and affective productions. Methodologically, the research opts for a triangulation of three information records. Firstly, 50 in-depth interviews with the population receiving the conditional cash transfer; secondly, a systematic observation process in field journals, and thirdly, the creation of an archive of secondary sources that is nourished by: technical and administrative reports on social policy in Colombia, documents and reports from multilateral organizations, impact evaluations, guides and material with which financial training processes are carried out for the recipients of the transfer money, among others. The article adopts a critical perspective that uses theoretical references from the French school of regulation, as well as some analyses of the work of Michel Foucault. The form of government that is established with this type of social policies, based on premises such as human capital and entrepreneurship, gives rise to complex plots that go from obedience to the conditions of monetary transfer; fixation on obtaining money; and the servitude that is fostered within the framework of conditions of structural poverty and inequality in Colombia.